The Effect of E-Learning, Student Facilitator and Explaining Model Learning and Self-Regulated Learning on 11th Grade Students Learning Outcomes of Economic Subject in Senior High School 1 Perbaungan School Year 2019/2020 - Eduward Situmorang; Saidun Hutasuhut; Indra Maipita (BIRCU, 2019)
This study aims to determine students taught by E-Learning and SFAE models obtain higher economic learning outcomes compared to SFAE models without E-Learning. The study is conducted in odd semester of Academic Year 2019/2020 in class XI of SMA Negeri 1 Perbaungan. The sampling technique of this study uses a cluster random sampling technique to establish an experimental group and a control group. The research approach is quantitative research with a quasi-experimental research design with non-equivalent (Pre Test and Post Test Design). The research design is pretest and posttest control design and the research design can be presented with a 2 x 2 factorial design with the Two Path Analysis of Variance (ANAVA) technique. The results shows that there is a difference between student learning outcomes in the E-Learning class + SFAE Learning Model, and student learning outcomes applied by the SFAE Learning Model model and students who gained the greatest influence from E-Learning + SFAE Learning Model on student economic learning outcomes, namely 0 , 0929. It means that E-Learning + SFAE Learning Model can explain 9.29% the effect of variations in the score of student learning outcomes.